Factor analysis of profit wholesale-retail pharmaceutical companies - I. A. Nechepurenko; V. V. Malyavina; A. M. Sampiev (Кубанский научный медицинский вестник)
The results of the analysis of the factors affecting the net profit and profitability of the pharmaceutical company. As an object of research performed one of the typical wholesale-retail pharmaceutical organizations. During the analysis found a negative effect on the value of absolute values of gross and net profit decrease in total turnover for 2009-2014 years. to 41.62%, revealed a compensatory effect on the value of the level of gross profit and net profit, changes in the structure of total turnover in the direction of increasing the proportion of groups with higher marginal income, and also demonstrated a negative effect on the growth of levels of financial performance costs.